Literatur Review: Cysteamine Terapi Terkini Hiperpigmentasi yang Menjanjikan - Mutia Taftila; Uswah Uswah; Yiesha Ariqah Vihsany (Jurnal Kesehatan Amanah, 2025)
Cysteamine, an aminothiol compound naturally produced in human cells, is emerging as an effective depigmenting agent to treat hyperpigmentation conditions such as melasma and lentigo. Although hydroquinone has become the gold standard in the treatment of melasma, its long-term use can cause serious side effects. Cysteamine offers a safer and effective alternative with mechanisms of action that include inhibition of the tyrosinase enzyme, increased glutathione levels, and keratolytic effects. Various studies have shown that cysteamine 5% cream is not only better tolerated compared to Kligman's Formula, but also shows equivalent or better ability in reducing Modified Melasma Area and Severity Index (mMASI) scores. In addition, cysteamine was also effective in treating lentigo, with significant results in the reduction of hyperpigmentation. Although there are tolerance-related challenges, especially the unpleasant odor, the potential efficacy and good safety profile make cysteamine a promising option in the treatment of hyperpigmentation. Further research is needed to optimize formulations and explore combination therapies for better results.